2019
DOI: 10.1148/radiol.2018181278
|View full text |Cite
|
Sign up to set email alerts
|

A Grading System for the Assessment of Risk of Extraprostatic Extension of Prostate Cancer at Multiparametric MRI

Abstract: To evaluate MRI features associated with pathologically defined extraprostatic extension (EPE) of prostate cancer and to propose an MRI grading system for pathologic EPE. Materials and Methods: In this prospective study, consecutive male study participants underwent preoperative 3.0-T MRI from June 2007 to March 2017 followed by robotic-assisted laparoscopic radical prostatectomy. An MRI-based EPE grading system was defined as follows: curvilinear contact length of 1.5 cm or capsular bulge and irregularity wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
134
2
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 163 publications
(157 citation statements)
references
References 35 publications
5
134
2
5
Order By: Relevance
“…Relative lesion volume (MRI‐lesion‐percentage) was calculated as a ratio of MRI‐lesion‐volume and Prostate‐size. Presence of extracapsular extension (EPE‐MRI) was reported using a previously developed system, specifically: EPE‐MRI grade 0 = no suspicion for pathologic extracapsular extension (EPE); EPE‐MRI grade 1 = either curvilinear contact length or capsular irregularity and bulge; EPE‐MRI grade 2 = both curvilinear contact length and capsular irregularity and bulge; EPE‐MRI grade 3 = frank EPE visible at MRI or invasion of adjacent anatomic structures. Seminal vesicle invasion (SVI‐MRI) was reported as positive when there was a loss of the normal high signal within the seminal vesicles .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Relative lesion volume (MRI‐lesion‐percentage) was calculated as a ratio of MRI‐lesion‐volume and Prostate‐size. Presence of extracapsular extension (EPE‐MRI) was reported using a previously developed system, specifically: EPE‐MRI grade 0 = no suspicion for pathologic extracapsular extension (EPE); EPE‐MRI grade 1 = either curvilinear contact length or capsular irregularity and bulge; EPE‐MRI grade 2 = both curvilinear contact length and capsular irregularity and bulge; EPE‐MRI grade 3 = frank EPE visible at MRI or invasion of adjacent anatomic structures. Seminal vesicle invasion (SVI‐MRI) was reported as positive when there was a loss of the normal high signal within the seminal vesicles .…”
Section: Methodsmentioning
confidence: 99%
“…Presence of extracapsular extension (EPE‐MRI) was reported using a previously developed system, specifically: EPE‐MRI grade 0 = no suspicion for pathologic extracapsular extension (EPE); EPE‐MRI grade 1 = either curvilinear contact length or capsular irregularity and bulge; EPE‐MRI grade 2 = both curvilinear contact length and capsular irregularity and bulge; EPE‐MRI grade 3 = frank EPE visible at MRI or invasion of adjacent anatomic structures. Seminal vesicle invasion (SVI‐MRI) was reported as positive when there was a loss of the normal high signal within the seminal vesicles . In order to evaluate interreader variability, a randomly selected 20% of the final study cohort ( n = 18) was re‐reported using the same reporting system by the second reader, Reader B (S.L., 10 years of prostate MRI experience), blinded to the reports of Reader A.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even more importantly, most of the studies did not de ne set criteria for assessing SVI and EPE regarding each of the components of PSMA-PET and MRI/CT, along with how to perform integrated interpretation of them. For MRI, several criteria for assessment of EPE (e.g., ESUR criteria, Mehralivand grading system, and length of tumor capsular contact) have been tested and validated in some studies [6,44,45]. Furthermore, recent efforts by multidisciplinary international group of experts, focused on proposing standardized assessment of PSMA-PET with the molecular imaging TNM system (miTNM, version 1.0) and PSMA reporting and data systems (PSMA-RADS) version 1.0; however, these systems have neither been tested nor validated in the literature [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Nomograms combining clinicopathological information including prostate-speci c antigen (PSA) levels, clinical stage based on digital rectal examination, and biopsy-related information (Gleason score, number and percentage of positive cores) are often used to predict the extent of prostate cancer [4]. However, there is an increasing number of studies showing that incorporating preoperative magnetic resonance imaging (MRI) results provide incremental value in predicting SVI and EPE [4][5][6][7]. Nevertheless, these results are still imperfect with area under the curves (AUC) ranging from 0.74-0.87 [8][9][10].…”
Section: Introductionmentioning
confidence: 99%